Development Marketplace : A Sillicon Valley for Development - Kuraishi, Mari (2012)
In 1999, as news of protesters being subdued with pepper spray in Seattle at the WTO Ministerial Conference came drifting in, we sat explaining our plans for the World Bank's first Development Marketplace to a senior member of the International Finance Corporation's innovation team.